Physoschistura chhimtuipuiensis, a new species of loach (Teleostei: Nemacheilidae) from Mizoram, north-eastern India - Lalramliana, Lalramliana; Lalhlimpuia, Denis Van; Solo, Beihrosa; Vanramliana, Vanramliana (Zootaxa, 2016)
Physoschistura chhimtuipuiensis, new species, from a tributary of the Kaladan River in Mizoram, northeastern India, is distinguished from all other species of Physoschistura by a combination of the following characters: scales between pectoral- and pelvic-fin bases deeply embedded and sparsely set, lateral line incomplete with 56–63 pores, reaching slightly beyond the base of the last anal-fin ray, a suborbital flap in male, 8½ branched dorsal-fin rays and 8+7 branched caudal-fin rays.